Suspended graphene oxide nanosheets maintain the self-renewal of mouse embryonic stem cells via down-regulating the expression of Vinculin. (July 2018) - Jing, Guoxin; Wang, Zhaojie; Zhuang, Xizhen; He, Xiaolie; Wu, Huijun; Wang, Qingxiu; Cheng, Liming; Liu, Zhongmin; Wang, Shilong; Zhu, Rongrong
Abstract: Graphene oxide (GO), with good hydrophilicity and biocompatibility, is widely explored as a carrier for various factors in the field of stem cell differentiation. However, its function of sustaining the stemness of mouse embryonic stem cells (mESCs) and the underlying mechanisms of this process remains undiscovered. Herein, we explored the biofunction of GO on mESCs and revealed the involved signaling pathways and key gene. The alkaline phosphatase activity detection, pluripotency genes quantification and the teratomas formation in vivo confirmed that GO nanosheets could sustain the self-renewal ability of mESCs instead of influencing its pluripotency. The underlying signaling pathways were uncovered by RNA-seq that integrin signaling pathway was involved in the biofunction of GO on mESCs and Vinculin turned to be a key gene for the effect of GO. Further experiments confirmed that the downregulation of Vinculin influenced the fate of mESCs through decreasing the expression of MEK1. Altogether, the study demonstrated for the first time that GOs hold the potential in sustaining the self-renewal of mESCs and clarified the mechanism of this function, which make it play a new role in stem cell research and regenerative medicine.